Analysis of wild sunflower (Helianthus annuus L.) root exudates using gas chromatography‐mass spectrometry. Issue 5 (20th August 2015) - Bowsher, Alan W.; Ali, Rifhat; Harding, Scott A.; Tsai, Chung‐Jui; Donovan, Lisa A.
Abstract Plant root systems mediate ecological processes in the rhizosphere through the exudation of organic compounds. Although exudate composition is thought to depend strongly on plant nutrient status, little is known about the influence of multi‐nutrient stresses. In this study, we examined responses to short‐term (3 d) nutrient limitation in Helianthus annuus (common sunflower), and root exudates were collected for 2, 4, or 6 h with the trap‐solution method. Root exudates, analyzed by means of gas chromatography‐mass spectrometry, consisted of over 60 sugars, sugar alcohols, amino acids, organic acids, and phosphates, with sugars and organic acids generally detected in the highest quantities. Twenty‐five of the detected metabolites, including half of the organic acids, sugars, and sugar alcohols, differed in relative abundance among the three sampling intervals, exhibiting higher abundance in sampling intervals greater than 2 h. Similarly, 24 of the detected metabolites, including half of the amino acids, phosphates, and sugar alcohols, were affected by nutrient supply, with 20 exhibiting higher abundance in the high‐nutrient treatment. Fumaric acid, quinic acid, and glucose were detected at significantly higher levels in the low‐nutrient treatment, potentially representing an adaptive response to nutrient limitation in sunflower. However, as sampling interval exerted a strong influence on the apparent effects of nutrient supply, future studies should consider the potential impacts of sampling‐interval length in comparative analyses of genotypes or treatments.